A CONJUNTURA DO FECHAMENTO E NUCLEAÇÃO DAS ESCOLAS DO CAMPO: ASPECTOS DETERMINANTES E CONSEQUÊNCIAS PARA A COMUNIDADE ESCOLAR - Primo, Samoel Cordeiro de Souza (2021)
The study presented in this dissertation sought to investigate the determining factors and the consequences of the closing and nucleation of Escolas do Campo. The specific objectives of this research were: a) to discuss the relationship between educational policies and the closing and nucleation of Escolas do Campo; b) carry out a literature review on the theoretical assumptions of Rural Education; c) produce notes on the determining aspects and consequences of the closing and nucleation of Rural Schools for the school community. The time frame of the research is limited to the period from 1995 to 2020. In addition to the considerations made about the closing and nucleation of Escolas do Campo, it presents the panorama of education in the municipality of Pitanga - PR, with emphasis on aspects of Rural Education. The research with a qualitative and quantitative approach includes a bibliographic study, a survey on the closing of Rural Schools in the CAPES database portal and a documental research. The research problem is based on the following formulation: What are the determining factors and consequences of the closing and nucleation of Escolas do Campo? These questions are answered throughout the text. A survey of the educational landscape of the municipality of Pitanga - PR was also carried out between 1995 and 2020, focusing on the Escolas do Campo closed in this period. The analysis of the determining aspects and the consequences of the closing and nucleation of the Rural Schools had as a methodological contribution the analysis of the conjuncture proposed by Souza (1984). The research was based on the assumptions of historical and dialectical materialism, understanding reality as a contradictory movement, marked by power relations, an important element in Souza's analysis (1984). Through this research it was possible to demonstrate that there are different factors that determine the closing and nucleation of Escolas do Campo. In the same way, the most varied consequences occur. Closing the Escola do e no Campo is not the solution to the educational problems present in the context of the peasant territory. Educational policies are needed for linking and belonging to rural peoples with the culture and the way they live in harmony with nature. In addition, it was possible to verify the relations and contradictions of the hegemonic capitalist project that reproduces and expands inequalities in the countryside. At this juncture, we also seek to highlight the reality experienced by students, workers and workers who fight for an education that meets the demands present in the countryside.